2019
DOI: 10.35940/ijitee.k2161.0981119
|View full text |Cite
|
Sign up to set email alerts
|

Building Management System

Abstract: A Building Management System is also known as Building Automation System (BAS), It is a Computer based control system installed in buildings that controls and monitors buildings mechanical and electrical equipment such as ventilation, lighting, power systems and security systems. A building management system for METRO includes inputs from the systems like HVAC (Heating Ventilation Air Conditioning), Lifts Escalators, UPS and Fire Alarm and Detection System etc. A Building Management system uses a PLC controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A study concludes that the scanning electron microscopy confirmed that quartz does not participate in geopolymerization and completely remains in the structure as fine particles. high-hardness quartz particles by retarding crack growth in the geopolymer matrix enhance the mechanical behavior of the samples [16,17]. Although quartz particles could potentially increase the compressive strength of geopolymers, the main factor determining the mechanical response of geopolymers is geopolymer gel, and to obtain the maximum compressive strength, appropriate thermal and alkaline activation of the source material is necessary [18].…”
Section: Resultsmentioning
confidence: 99%
“…A study concludes that the scanning electron microscopy confirmed that quartz does not participate in geopolymerization and completely remains in the structure as fine particles. high-hardness quartz particles by retarding crack growth in the geopolymer matrix enhance the mechanical behavior of the samples [16,17]. Although quartz particles could potentially increase the compressive strength of geopolymers, the main factor determining the mechanical response of geopolymers is geopolymer gel, and to obtain the maximum compressive strength, appropriate thermal and alkaline activation of the source material is necessary [18].…”
Section: Resultsmentioning
confidence: 99%
“…found that many authors used Kinect in their studies,Beena et al (2019);Prathap & Kumar (2019);Raghuveera et al (2019);Ravi et al (2019);Hisham & Hamouda (2019);Sidig et al (2019);Elpeltagy et al (2018); Sidiq et al (2021). Kinect uses sensors and a camera to collect coloured pictures of objects, including their depths.…”
mentioning
confidence: 99%